Ru/Mo2C@NC Schottky junction-loaded hollow nanospheres as an efficient hydrogen evolution electrocatalyst. Issue 36 (1st September 2021) - Salah, Abdulwahab; Ren, Hong-Da; Al-Ansi, Nabilah; Yu, Fei-Yang; Lang, Zhong-Ling; Tan, Huaqiao; Li, Yang-Guang
Abstract : A new electrocatalyst, N-doped carbon hollow nanospheres loaded with Ru/Mo2 C Schottky junctions (Ru/Mo2 C@NC), exhibits superior hydrogen evolution performance to commercial Pt/C in a universal pH range. Abstract : The development and design of low-cost, high-performance catalysts with small overpotentials for hydrogen evolution in the universal-pH range still represent defiance for replacing the high-cost Pt metal catalysts and future energy technology. Herein, we designed a new electrocatalyst, N-doped carbon hollow nanospheres loaded with Ru/Mo2 C Schottky junctions (denoted as Ru/Mo2 C@NC), through a one-step approach by polymerization-induced self-assembly of a Mo–polydopamine hollow framework modified with ruthenium (Ru) in alkaline solution followed by in situ carbonization at high temperature. In 1 M KOH, the Ru/Mo2 C@NC (Ru wt% = 3.93%) catalyst exhibits superb HER activity with a small overpotential at 10 mA cm −2 ( η 10 = 13 mV), a low Tafel slope of 33.24 mV dec −1, and long-term temporal stability for 72 h. Besides, the fabricated catalyst also displays low overpotentials of 21 and 41 mV to realize 10 mA cm −2 in both 0.5 M H2 SO4 and 1 M PBS media, respectively, which are smaller and better than those of 20% Pt/C (26 and 59 mV). According to density functional theory (DFT) calculations, the introduction of metallic Ru into Mo2 C has succeeded in constructing new active sites for H with optimal adsorption/desorption ability (Δ G H* = −0.09 eV) and maintaining relatively low water dissociation (Δ G b = 0.35 eV) in alkaline medium, endowing the composite with superb HER activity in the universal-pH range. Additionally, the outstanding catalytic HER performance is also fundamentally related to the effective influence of separating and transferring electrons from Mo2 C to Ru via the Schottky junction.